Analysis of Corrosion Rate in Low-Carbon Steel ASTM A36 and AISI 1020 in Sulfuric Acid Solution Using Heat Treatment Temperature and Immersion Time Variations - Wiradinata, Trisna Ardi; Daryus, Asy'ari; Sugiyanto, Didik; Nopryandi; Ikhsan, Muhammad (Jurnal Konversi Energi dan Manufaktur, 2025)
This study investigates the corrosion rate of low-carbon steel ASTM A36 and AISI 1020 in sulfuric acid solution under varying heat treatment temperatures and immersion times. Samples were subjected to heat treatment at 600, 820, and 1100 °C, followed by immersion for 24, 48, and 72 hours. The results reveal significant effects of heat treatment temperature and immersion duration on corrosion performance. At 600 °C with a 72-hour immersion, ASTM A36 exhibited a corrosion rate of 140.68 mm/year, while AISI 1020 showed 149.07 mm/year. At 820 °C, the corrosion rates for ASTM A36 and AISI 1020 were 102.34 mm/year and 96.48 mm/year, respectively. At 1100 °C, ASTM A36 demonstrated a corrosion rate of 87.97 mm/year, compared to 121.08 mm/year for AISI 1020. The findings highlight that increasing heat treatment temperature generally reduces the corrosion rate, though the effect varies by material.